2009
DOI: 10.1007/s00384-009-0784-1
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer in Iran: immunohistochemical profiles of four mismatch repair proteins

Abstract: Along with the recommendations of the National Institute of Cancer, we recommend immunohistochemistry staining for MLH1, MSH2, PMS2, and MSH6 for determining the eligibility of patients for mutation analysis of MMR genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
3
12
2
Order By: Relevance
“…[13][14][15][16][17] Proximal tumors, which have long been associated with the MSI phenotype, were significantly overrepresented in this group. 4 Fifteen tumors had LoE of one or both components of the MLH1-PMS2 heterodimer, and the 18 had LoE of one or both components of the MSH2-MSH6 heterodimer.…”
Section: Discussionmentioning
confidence: 89%
“…[13][14][15][16][17] Proximal tumors, which have long been associated with the MSI phenotype, were significantly overrepresented in this group. 4 Fifteen tumors had LoE of one or both components of the MLH1-PMS2 heterodimer, and the 18 had LoE of one or both components of the MSH2-MSH6 heterodimer.…”
Section: Discussionmentioning
confidence: 89%
“…Immunohistochemical staining for products of mismatch repair genes, MLH1, MSH2 and MSH6, was done according to a previously described method [15]. Intramucosal lymphocytes were used as positive controls.…”
Section: Methodsmentioning
confidence: 99%
“…The basic tests identify five markers (NR-21, BAT-26, BA T -25, NR-27 and NR-24) to devise the simplest diagnostic assay (9). Previous reports have shown significant diversity regarding the most common marker for microsatellite testing; BAT 25, BAT26 and NR21 have been reported in HNPCC and sporadic CRCs (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Table 1 shows the reports from Iran that studied the frequency of MMR genes in both hereditary and sporadic colorectal cancers.…”
Section: Microsatellite Instability (Msi)mentioning
confidence: 99%
“…Table 1 shows the reports from Iran that studied the frequency of MMR genes in both hereditary and sporadic colorectal cancers. As it shows, the frequency of MSI in patients with HNPCC has been 29% -62.5% (9-25), there are not so many studies about the frequency of MSI in sporadic CRC from Iran; however, the reported frequencies of MMR have been from 19.4% to 66.6% (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Microsatellite Instability (Msi)mentioning
confidence: 99%